Silicate composite copper-manganese spinel catalytic material and preparation method and use thereof

CN118341414BActive Publication Date: 2026-10-30ZHONGYE-CHANGTIAN INT ENG CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202410532895.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-29
Publication Date
2026-10-30
Estimated Expiration
2044-04-29

AI Technical Summary

Technical Problem

[0005]针对现有技术中,现有催化剂在对烟气中的CO进行催化氧化时存在抗硫、抗积碳性能差进而导致催化剂中毒的问题,本发明提供了一种硅酸盐复合铜锰尖晶石催化材料及其制备方法和用途,该硅酸盐复合铜锰尖晶石催化材料通过异价取代的方式在铜锰尖晶石上复合了硅酸钠,进而在催化剂材料表面形成保护层的同时产生大量的非对称型氧空位,可显著减少对烟气中SO2和苯的吸附,促进含碳副产物的氧化分解与脱附,从而达到同时具备抗硫、抗积碳的效果

Benefits of technology

[0033]在本发明中,在硅重组后通过再次煅烧处理,可进一步促进CuMn尖晶石和硅酸钠之间的元素相互取代与紧密结合,进而有助于提高催化性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118341414B_ABST
    Figure CN118341414B_ABST
Patent Text Reader

Abstract

The application discloses a silicate composite cupric-manganese spinel catalytic material and a preparation method and application thereof. In the preparation of the cupric-manganese spinel, a silicon source is added to pre-combine silicon, and then the pre-combined Si element is recombined with concentrated alkali to form silicate and is loaded on the surface of the cupric-manganese spinel, so that a large number of Ov are generated while a protective layer is formed, and the sulfur resistance and carbon deposition resistance of the catalytic material are significantly improved, and the catalytic stability of the catalytic material is greatly improved. In addition, the catalytic material has the advantages of stable catalytic performance, high low-temperature activity, and excellent catalytic oxidation effect on CO in sintering flue gas, and the preparation method is simple and short, and has wide market prospect and significant economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to CO catalytic materials, specifically to a silicate composite copper-manganese spinel catalytic material, its preparation method, and its applications, belonging to the field of CO catalysis technology. Background Technology

[0002] Carbon monoxide (CO) is a colorless, odorless, and non-irritating combustible toxic gas. Low concentrations of CO emitted into the atmosphere can cause ozone pollution, and inhalation can lead to cardiovascular diseases, posing a significant threat to human living environments and health. CO originates from the incomplete combustion of fossil fuels, and its emission sources include stationary sources (such as steel plant exhaust and cement plant exhaust) and mobile sources (such as vehicle exhaust and ship exhaust). Among stationary CO emission sources, steel plant exhaust accounts for approximately 30%. Tangshan, Linfen, and other regions have already implemented CO emission limits for the steel industry, thus highlighting the urgent need for CO control measures in this sector.

[0003] The CO volume fraction in steel flue gas is between 0.5% and 0.8%, making it suitable for oxidative removal using catalysts. Copper-manganese catalysts are widely used in CO oxidation reactions. Copper serves as a CO adsorption site; while manganese reacts with copper to form Cu. 2+ +Mn 3+ Cu + +Mn 4+ Circulation can not only promote Cu + The formation of copper manganese oxide enhances the catalyst's ability to adsorb CO and increases its oxygen activity, promoting redox reactions. Furthermore, when copper manganese oxide forms a spinel structure, it possesses numerous lattice defects, creating multiple active sites and exhibiting excellent catalytic activity. However, copper manganese catalysts readily react with sulfur in flue gas, forming sulfites and sulfates that coat the catalyst surface, causing sulfur poisoning. Especially in flue gas with high oxygen and water content, stable large-scale sulfates form, occupying active sites and clogging catalyst pores. In addition, benzene and CO in the flue gas form carbon deposits during the reaction, easily causing rapid catalyst deactivation. This is because copper manganese catalysts adsorb and catalyze benzene, causing benzene to occupy the active sites that should be used for CO oxidation, reducing site utilization and catalyst activity. More importantly, incomplete oxidation of benzene also forms carbon deposits covering active sites, causing poisoning. Furthermore, during the catalytic CO oxidation reaction, CO undergoes the Boudouard side reaction, forming elemental C(2CO₂)₂. (C + CO2); In addition to elemental C, various carbonates formed during CO oxidation can also chelate onto the catalyst surface, causing catalyst carbon poisoning. Carbon deposits on the surface of conventional catalysts generally require high temperatures of around 500℃ to oxidize and decompose, but are difficult to decompose at reaction temperatures of 200~300℃.

[0004] Existing technologies have made numerous improvements to the activity and stability of copper-manganese catalysts. CN113145125B employs a sol-gel method combined with freeze-drying to load copper-manganese onto a sodium silicate support, optimizing the pore structure and metal ion dispersion, thereby improving the catalyst's activity and stability in ozone oxidation of organic pollutants in wastewater. CN102688765B uses a bauxite-supported copper-manganese catalyst for water-gas shift conversion, improving its thermal stability. CN109603842B uses a La-doped copper-manganese catalyst, improving its low-temperature activity and thermal stability for VOCs oxidation. CN112547085B prepares a copper-manganese spinel catalyst modified with copper-manganese oxides, improving its low-temperature CO oxidation activity. CN113046778B uses ammonia etching of copper-manganese spinel to dissolve some copper, exposing more manganese active centers, resulting in an electrocatalytic material with excellent performance. However, none of the existing technical solutions mention how to simultaneously address the issues of sulfur resistance and carbon buildup. In actual sintering flue gas applications, sulfur poisoning caused by SO2 and carbon buildup caused by benzene-based VOCs and CO side reactions are issues that need to be considered simultaneously. Summary of the Invention

[0005] To address the problem that existing catalysts exhibit poor resistance to sulfur and carbon deposition during the catalytic oxidation of CO in flue gas, leading to catalyst poisoning, this invention provides a silicate composite copper-manganese spinel catalyst material, its preparation method, and its applications. This silicate composite copper-manganese spinel catalyst material incorporates sodium silicate onto copper-manganese spinel through anisovalent substitution, thereby forming a protective layer on the catalyst material surface and generating a large number of asymmetric oxygen vacancies. This significantly reduces the adsorption of SO2 and benzene in flue gas and promotes the oxidative decomposition and desorption of carbon-containing byproducts, thus achieving both sulfur and carbon deposition resistance.

[0006] To achieve the above-mentioned technical objectives, the technical solution adopted by the present invention is as follows: According to a first embodiment of the present invention, a silicate composite copper-manganese spinel catalyst is provided: A silicate-composite copper-manganese spinel catalytic material is obtained by composite silicate onto copper-manganese spinel through anisovalent substitution.

[0007] Preferably, the copper-manganese spinel has the chemical formula Cu. x Mn y O z Where x takes values ​​from 1 to 3, y takes values ​​from 1 to 4, and z takes values ​​from 3 to 12.

[0008] Preferably, the silicate is one or more of lithium silicate, sodium silicate, and potassium silicate, with sodium silicate being the most preferred.

[0009] Preferably, in the catalytic material, the composite molar ratio of copper manganese spinel to sodium silicate is 1:0.05~0.5, more preferably 1:0.1~0.3.

[0010] According to a second embodiment of the present invention, a method for preparing a silicate composite copper-manganese spinel catalyst is provided: A method for preparing a silicate composite copper-manganese spinel catalytic material, or a method for preparing a silicate composite copper-manganese spinel catalytic material as described in the first embodiment, the method comprising the following steps: 1) A mixed solution is obtained by dissolving copper source, manganese source and silicon source in solvent.

[0011] 2) Add an alkaline precipitant to the mixed solution to carry out the reaction. After the reaction is completed, perform solid-liquid separation and calcine the obtained solid product to obtain the crude product.

[0012] 3) First, the crude product is placed in an alkaline solution for reaction. After the reaction is completed, it is calcined to obtain a silicate composite copper-manganese spinel catalyst material.

[0013] Preferably, in step 1), the copper source is a soluble copper salt, preferably one or more of copper sulfate, copper nitrate, copper chloride, and copper acetate, and more preferably copper acetate.

[0014] Preferably, in step 1), the manganese source is a soluble manganese salt, preferably one or more of manganese sulfate, manganese nitrate, manganese chloride, and manganese acetate, with manganese acetate being the most preferred.

[0015] Preferably, in step 1), the silicon source is silicon dioxide, preferably silicon dioxide nanoparticles.

[0016] Preferably, in step 1), the solvent is a mixture of water and ethanol. Preferably, the molar ratio of water to ethanol in the mixture is 1-2.5:0.1-1.

[0017] Preferably, in step 1), the molar ratio of copper source, manganese source and silicon source in the mixed solution is 0.8~2:0.8~2:1~6, and more preferably 1~1.5:1~1.5:2~5.

[0018] Preferably, in step 2), the alkaline precipitant is ammonia. The amount of ammonia added is 2 to 7 times the total molar amount of the copper and manganese sources, preferably 3 to 6 times.

[0019] Preferably, in step 2), the calcination temperature is 350~550℃, more preferably 400~500℃. The calcination time is 1~12h, more preferably 2~10h.

[0020] Preferably, in step 3), the alkaline solution is an aqueous solution of lithium hydroxide, sodium hydroxide, potassium hydroxide, and calcium hydroxide. Preferably, it is a sodium hydroxide solution with a concentration of not less than 1 mol / L, more preferably a sodium hydroxide solution with a concentration of 1.5~5 mol / L. The amount of alkaline solution added is such that the molar ratio of silicon to alkali in the crude product is 1~3.5:3~10, preferably 1.3~3:4~9.

[0021] Preferably, in step 3), the calcination temperature is 350~550℃, more preferably 400~500℃. The calcination time is 1~12h, more preferably 2~10h.

[0022] Preferably, in step 3), the reaction temperature of the crude product in the alkaline solution is 40-80°C, more preferably 50-70°C. The reaction time is 0.3-2 hours, more preferably 0.5-1.5 hours.

[0023] Preferably, steps 1) to 3) are as follows: First, the copper source, manganese source, and silicon source are weighed according to the specified ratio and added to a sufficient amount of solvent. After stirring and dissolving evenly, a mixed solution is obtained. Then, an alkaline precipitant is added dropwise to the mixed solution under stirring to carry out the reaction. After the reaction is completed, the mixture is filtered to obtain a solid product. The solid product is washed until neutral and dried at 40-200°C, followed by calcination to obtain a crude product. Finally, the crude product is placed in an alkaline solution under heating to carry out the reaction. After the reaction is completed, the mixture is filtered to obtain a precursor. The precursor is washed until neutral and dried at 40-200°C, followed by calcination to obtain a silicate composite copper-manganese spinel catalyst material.

[0024] According to a third embodiment of the present invention, an application of a silicate composite copper-manganese spinel catalyst is provided: The use of a silicate composite copper-manganese spinel catalyst material, or a silicate composite copper-manganese spinel catalyst material prepared by the method described in the first embodiment or the method described in the second embodiment, for the catalytic oxidation of CO.

[0025] Preferably, the silicate composite copper-manganese spinel catalyst is used for the catalytic oxidation of CO in sintering flue gas.

[0026] In this invention, the catalytic material continuously catalyzes the oxidation of CO in sintering flue gas containing water, SO2, and benzene-based VOCs. Its effective anti-sulfur and anti-carbon deposition lifespan is not less than 90 days (after testing, it was found that the anti-sulfur and anti-carbon deposition performance of the catalytic material is still maintained at 90-95% or more after 90 days).

[0027] In actual operating conditions, the flue gas from steel sintering contains high levels of sulfur dioxide and benzene-based VOCs, as well as a large amount of oxygen and moisture. Ordinary catalysts are prone to sulfur poisoning and carbon deposition when catalytically oxidizing CO in this flue gas, leading to catalyst deactivation. The silicate composite copper-manganese spinel catalyst provided by this invention forms silicates (such as sodium silicate) on copper-manganese spinel through anisovalent substitution. Specifically, by using a special method to load silicates, a protective layer is formed on the catalyst surface, generating a large number of asymmetric oxygen vacancies (Ov). This significantly reduces the adsorption of SO2 and benzene, while promoting the oxidative decomposition and desorption of carbonaceous byproducts, thereby achieving anti-sulfur and anti-carbon deposition effects and significantly improving the catalytic stability of the catalyst.

[0028] In this invention, the preparation process of the silicate composite copper-manganese spinel catalyst is as follows: First, a copper source (such as copper acetate), a manganese source (such as manganese acetate), and a silicon source (such as SiO2) are simultaneously dissolved in a solvent to obtain a mixed solution. Then, an alkaline precipitant is added dropwise to the mixed solution, and precipitation and crystallization occur at room temperature. After filtration, washing, drying, and calcination, copper-manganese spinel containing Si (such as Cu) is obtained. 1.5 Mn 1.5 The product is O4; then, the spinel product is treated with concentrated alkali to recombine the Si element, and after filtration, washing, drying, and calcination, the copper-manganese spinel product loaded with sodium silicate is obtained. Finally, the above catalyst material is used in sintering flue gas containing water, SO2, and VOCs, and can stably catalyze the oxidation of CO without deactivation due to the presence of SO2 and benzene-based VOCs, exhibiting high catalytic stability.

[0029] In this invention, a silicon source (e.g., SiO2) is added during the preparation of copper-manganese spinel. Since SiO2 nanoparticles can be uniformly dispersed in water, copper and manganese precipitate and crystallize uniformly around the monodisperse SiO2 nanoparticles, promoting the uniform and abundant formation of the Cu-O-Si / Mn-O-Si interface. Because spinel nanoparticles are prone to agglomeration and cannot be monodisperse like SiO2, preparing spinel first and then loading silicon cannot achieve uniform doping; therefore, silicon salts need to be added during the preparation of copper-manganese spinel. Pre-composite treatment is then performed using concentrated alkali. Si, on the one hand, forms a sodium silicate thin film protective layer loaded on copper-manganese spinel nanosheets, mitigating sulfur corrosion and hindering the adsorption of benzene-based VOCs. On the other hand, through anisovalent substitution (it should be noted that anisovalent substitution is the opposite of equivalent substitution, referring to replacing elements in the parent structure with elements of different valence states. To maintain electroneutrality, charge transfer occurs continuously between the two elements, thereby promoting oxygen adsorption and conduction. Therefore, anisovalent substitution can improve the physical and chemical properties of the parent structure to a greater extent while maintaining it), induces lattice distortion to form Ov, promoting oxygen conduction and low-temperature decomposition of carbon deposits. The anisovalent substitution of Si for Cu and Mn can form Si-Ov-Mn and Si-Ov-Cu structures, where Ov represents a stable oxygen vacancy that can continuously conduct oxygen. Simultaneously, concentrated alkali, while recombining Si, also introduces defects into the catalyst by dissolving some Cu, forming Cu-Ov-Mn asymmetric oxygen vacancies, which also promote carbon decomposition. Furthermore, when concentrated alkali reorganizes Si and dissolves some Cu, it forms channels in the catalyst, increasing the surface area and facilitating reactant diffusion and adsorption, as well as byproduct desorption. Through this process, the catalytic material exhibits high activity at low temperatures and can resist sulfur and carbon deposition in flue gas containing water, SO2, and VOCs, thus stabilizing the catalytic oxidation of CO.

[0030] In this invention, the purpose of adding an alkaline precipitant is to uniformly form CuMn hydroxide precipitate on the surface and periphery of SiO2 nanoparticles. The purpose of the first calcination is to transform the CuMn hydroxide precipitate into CuMn spinel.

[0031] In this invention, concentrated alkali is used to recombine Si elements in the crude product. The purpose is to recombine SiO2 into sodium silicate while simultaneously etching spinel and dissolving some Cu, allowing sodium silicate molecules to tightly bond with the spinel through the etching defects, forming more Cu-O-Si / Mn-O-Si interfaces. Directly soaking and adsorbing silicates with copper-manganese spinel cannot achieve the same effect. It should be noted that the concentration of concentrated alkali for Si recombination needs strict control, generally between 1 and 5 mol / L. If the alkali concentration is too low, the SiO2 recombination into sodium silicate reaction is difficult to occur; if the alkali concentration is too high, Cu will dissolve excessively, leading to the loss of active components. Furthermore, during the recombination reaction, a reaction time that is too short will result in insufficient SiO2 recombination; a reaction time that is too long will lead to excessive dissolution of the active component Cu.

[0032] In this invention, the Si element recombination temperature of the crude product using concentrated alkali is generally 40-80℃, and the temperature should not be too low or too high. If the temperature is below 40℃, the SiO2 recombination reaction is difficult to occur; if the temperature is above 80℃, NaOH will excessively dissolve most of the Cu, leading to the loss of active components. The optimal reaction temperature range is 50-70℃, and the reaction time is 0.5-1.5 hours. It should be noted that, similar to the principle of reaction temperature control, if the reaction time is too short, the SiO2 recombination will be insufficient; if the reaction time is too long, Cu may be excessively dissolved.

[0033] In this invention, after silicon recombination, a second calcination treatment can further promote the elemental substitution and tight bonding between CuMn spinel and sodium silicate, thereby helping to improve catalytic performance.

[0034] Compared with the prior art, the beneficial technical effects of the present invention are as follows: 1. This invention adds a silicon source during the preparation of copper-manganese spinel to perform pre-composite silicon formation. Simultaneously, concentrated alkali is used to recombine the pre-composite Si elements to form silicates, which are then loaded onto the surface of the copper-manganese spinel to form a protective layer and generate a large amount of Ov. This significantly improves the sulfur resistance and carbon deposition resistance of the catalytic material and greatly enhances its catalytic stability.

[0035] 2. The catalytic material prepared by this invention has stable catalytic performance and high low-temperature activity. In particular, it has excellent catalytic oxidation effect on CO in sintering flue gas. Its preparation method is simple and the process is short, which has broad market prospects and significant economic benefits. Attached Figure Description

[0036] Figure 1 This is a scanning electron microscope (SEM) energy dispersive spectroscopy (EDS) image of the silicate composite copper-manganese spinel catalyst material of Example 1 of the present invention.

[0037] Figure 2 This is a transmission electron microscope (TEM) image of the silicate composite copper-manganese spinel catalytic material of Example 1 of the present invention.

[0038] Figure 3 The image shows the Raman spectrum of the silicate composite copper-manganese spinel catalyst material of Example 1 of this invention.

[0039] Figure 4 The image shows the XRD pattern of the silicate composite copper-manganese spinel catalyst material of Example 1 of this invention.

[0040] Figure 5 This is a process flow diagram of the present invention. Detailed Implementation

[0041] The technical solution of the present invention will be illustrated below with examples. The scope of protection sought by the present invention includes, but is not limited to, the following embodiments. Example 1

[0042] Copper acetate, manganese acetate, and silicon dioxide were weighed in a molar ratio of 1:1:4.7 and added to a sufficient amount of mixed solvent (water to ethanol molar ratio of 1:0.3). The mixture was stirred until dissolved and homogeneous to obtain a mixed solution. Then, under stirring, ammonia water (3 times the total molar amount of copper and manganese sources) was added dropwise to the mixed solution to initiate a precipitation reaction (at room temperature). After the reaction was complete, the solid product was obtained by filtration. The solid product was washed until neutral and dried at 60°C. It was then transferred to a calcining furnace and calcined at 400°C for 4 hours to obtain a crude product. Finally, the crude product was placed in a 2 mol / L sodium hydroxide solution at 60°C and reacted for 60 minutes (silicon to sodium hydroxide molar ratio of 1:4). After the reaction was complete, the precursor was obtained by filtration. The precursor was washed until neutral and dried at 60°C. It was then transferred to a calcining furnace and calcined at 400°C for 4 hours to obtain a silicate composite copper-manganese spinel catalyst.

[0043] Scanning electron microscopy energy dispersive spectroscopy (SEM) images of silicate composite copper-manganese spinel catalysts ( Figure 1 As can be seen from the transmission electron microscope (TEM), the catalytic material prepared in this embodiment contains copper, manganese, silicon, sodium, and oxygen elements. Figure 2 Raman spectroscopy Figure 3 ) and XRD pattern ( Figure 4 The catalyst contains copper-manganese spinel. Example 2

[0044] Copper nitrate, manganese nitrate, and silicon dioxide were weighed in a molar ratio of 1:1:4.7 and added to a sufficient amount of mixed solvent (water to ethanol molar ratio of 1:0.3). The mixture was stirred until dissolved and homogeneous to obtain a mixed solution. Then, under stirring, ammonia water (3 times the total molar amount of copper and manganese sources) was added dropwise to the mixed solution to initiate a precipitation reaction (at room temperature). After the reaction was complete, the solid product was filtered to obtain a solid product. The solid product was washed until neutral and dried at 60°C. It was then transferred to a calcining furnace and calcined at 400°C for 4 hours to obtain a crude product. Finally, the crude product was placed in a 2 mol / L sodium hydroxide solution at 60°C and reacted for 60 minutes (silicon to sodium hydroxide molar ratio of 1:4). After the reaction was complete, the precursor was filtered to obtain a precursor. The precursor was washed until neutral and dried at 60°C. It was then transferred to a calcining furnace and calcined at 400°C for 4 hours to obtain a silicate composite copper-manganese spinel catalyst. Example 3

[0045] Example 1 was repeated, except that the molar ratio of copper acetate, manganese acetate, and silicon dioxide was 1:1:4.2. Example 4

[0046] Repeat Example 1, except that the concentration of sodium hydroxide is 1.6 mol / L. Example 5

[0047] Repeat Example 1, except that the crude product was kept in a 2 mol / L sodium hydroxide solution for 90 min. Example 6

[0048] Repeat Example 1, except that the crude product was placed in a 2 mol / L sodium hydroxide solution at 50°C and reacted for 60 min.

[0049] Comparative Example 1 Copper acetate, manganese acetate, and silicon dioxide were weighed in a molar ratio of 1:1:4.7 and added to a sufficient amount of mixed solvent (water to ethanol molar ratio of 1:0.3). After stirring and dissolving evenly, a mixed solution was obtained. Then, under stirring, ammonia water was added dropwise to the mixed solution at a ratio of 3 times the total molar amount of copper and manganese sources to carry out a precipitation reaction (at room temperature). After the reaction was completed, the product was filtered to obtain a solid product. The solid product was washed until neutral and dried at 60°C. Then, it was transferred to a calcination furnace and calcined at 400°C for 4 hours to obtain the catalyst material.

[0050] Comparative Example 2 Copper acetate and manganese acetate were weighed at a molar ratio of 1:1 and added to a sufficient amount of mixed solvent (water to ethanol molar ratio of 1:0.3). The mixture was stirred until dissolved and homogeneous to obtain a mixed solution. Then, under stirring, ammonia water (3 times the total molar amount of copper and manganese sources) was added dropwise to the mixed solution to initiate a precipitation reaction (at room temperature). After the reaction was complete, the product was filtered to obtain a solid product. The solid product was washed until neutral and then impregnated in a silica dispersion. After impregnation, it was dried at 60°C and then transferred to a calcining furnace and calcined at 400°C for 4 hours to obtain a crude product. Finally, the crude product was placed in a 2 mol / L sodium hydroxide solution at 60°C and reacted for 60 minutes (silicon to sodium hydroxide molar ratio of 1:4). After the reaction was complete, the product was filtered to obtain a precursor. The precursor was washed until neutral and dried at 60°C and then transferred to a calcining furnace and calcined at 400°C for 4 hours to obtain the catalyst material.

[0051] Comparative Example 3 Copper acetate, manganese acetate, and silicon dioxide were weighed in a molar ratio of 1:1:0.3 and added to a sufficient amount of mixed solvent (water to ethanol molar ratio of 1:0.3). The mixture was stirred until dissolved and homogeneous to obtain a mixed solution. Then, under stirring, ammonia water (3 times the total molar amount of copper and manganese sources) was added dropwise to the mixed solution to initiate a precipitation reaction (at room temperature). After the reaction was complete, the solid product was filtered to obtain a solid product. The solid product was washed until neutral and dried at 60°C. It was then transferred to a calcining furnace and calcined at 400°C for 4 hours to obtain a crude product. Finally, the crude product was placed in a 2 mol / L sodium hydroxide solution at 60°C and reacted for 60 minutes (silicon to sodium hydroxide molar ratio of 1:4). After the reaction was complete, the precursor was filtered to obtain a precursor. The precursor was washed until neutral and dried at 60°C. It was then transferred to a calcining furnace and calcined at 400°C for 4 hours to obtain the catalyst material.

[0052] Comparative Example 4 Copper acetate, manganese acetate, and silicon dioxide were weighed in a molar ratio of 1:1:10 and added to a sufficient amount of mixed solvent (water to ethanol molar ratio of 1:0.3). The mixture was stirred until dissolved and homogeneous to obtain a mixed solution. Then, under stirring, ammonia water (3 times the total molar amount of copper and manganese sources) was added dropwise to the mixed solution to initiate a precipitation reaction (at room temperature). After the reaction was complete, the solid product was filtered to obtain a solid product. The solid product was washed until neutral and dried at 60°C. It was then transferred to a calcining furnace and calcined at 400°C for 4 hours to obtain a crude product. Finally, the crude product was placed in a 2 mol / L sodium hydroxide solution at 60°C and reacted for 60 minutes (crude product to sodium hydroxide molar ratio of 1:4). After the reaction was complete, the precursor was filtered to obtain a precursor. The precursor was washed until neutral and dried at 60°C. It was then transferred to a calcining furnace and calcined at 400°C for 4 hours to obtain the catalyst material.

[0053] Comparative Example 5 Copper acetate, manganese acetate, and silicon dioxide were weighed in a molar ratio of 1:1:4.7 and added to a sufficient amount of mixed solvent (water to ethanol molar ratio of 1:0.3). The mixture was stirred until dissolved and homogeneous to obtain a mixed solution. Then, under stirring, ammonia water (3 times the total molar amount of copper and manganese sources) was added dropwise to the mixed solution to initiate a precipitation reaction (at room temperature). After the reaction was complete, the solid product was filtered to obtain a solid product. The solid product was washed until neutral and dried at 60°C. It was then transferred to a calcining furnace and calcined at 400°C for 4 hours to obtain a crude product. Finally, the crude product was placed in a 0.2 mol / L sodium hydroxide solution at 60°C and reacted for 60 minutes (crude product to sodium hydroxide molar ratio of 1:4). After the reaction was complete, the precursor was filtered to obtain a precursor. The precursor was washed until neutral and dried at 60°C. It was then transferred to a calcining furnace and calcined at 400°C for 4 hours to obtain the catalyst material.

[0054] Comparative Example 6 Copper acetate, manganese acetate, and silicon dioxide were weighed in a molar ratio of 1:1:4.7 and added to a sufficient amount of mixed solvent (water to ethanol molar ratio of 1:0.3). The mixture was stirred until dissolved and homogeneous to obtain a mixed solution. Then, under stirring, ammonia water (3 times the total molar amount of copper and manganese sources) was added dropwise to the mixed solution to initiate a precipitation reaction (at room temperature). After the reaction was complete, the solid product was obtained by filtration. The solid product was washed until neutral and dried at 60°C. It was then transferred to a calcining furnace and calcined at 400°C for 4 hours to obtain a crude product. Finally, the crude product was placed in a 10 mol / L sodium hydroxide solution at 60°C and reacted for 60 minutes (crude product to sodium hydroxide molar ratio of 1:4). After the reaction was complete, the precursor was obtained by filtration. The precursor was washed until neutral and dried at 60°C. It was then transferred to a calcining furnace and calcined at 400°C for 4 hours to obtain the catalyst material.

[0055] Comparative Example 7 Copper acetate, manganese acetate, and silicon dioxide were weighed in a molar ratio of 1:1:4.7 and added to a sufficient amount of mixed solvent (water to ethanol molar ratio of 1:0.3). The mixture was stirred until dissolved and homogeneous to obtain a mixed solution. Then, under stirring, ammonia water (3 times the total molar amount of copper and manganese sources) was added dropwise to the mixed solution to initiate a precipitation reaction (at room temperature). After the reaction was complete, the solid product was filtered to obtain a solid product. The solid product was washed until neutral and dried at 60°C. It was then transferred to a calcining furnace and calcined at 400°C for 4 hours to obtain a crude product. Finally, the crude product was placed in a 2 mol / L sodium hydroxide solution at 60°C and reacted for 150 minutes (crude product to sodium hydroxide molar ratio of 1:4). After the reaction was complete, the precursor was filtered to obtain a precursor. The precursor was washed until neutral and dried at 60°C. It was then transferred to a calcining furnace and calcined at 400°C for 4 hours to obtain the catalyst material.

[0056] Comparative Example 8 Copper acetate, manganese acetate, and silicon dioxide were weighed in a molar ratio of 1:1:4.7 and added to a sufficient amount of mixed solvent (water to ethanol molar ratio of 1:0.3). The mixture was stirred until dissolved and homogeneous to obtain a mixed solution. Then, under stirring, ammonia water (3 times the total molar amount of copper and manganese sources) was added dropwise to the mixed solution to initiate a precipitation reaction (at room temperature). After the reaction was complete, the solid product was obtained by filtration. The solid product was washed until neutral and dried at 60°C. It was then transferred to a calcining furnace and calcined at 400°C for 4 hours to obtain a crude product. Finally, the crude product was placed in a 2 mol / L sodium hydroxide solution at 60°C and reacted for 3 minutes (crude product to sodium hydroxide molar ratio of 1:4). After the reaction was complete, the precursor was obtained by filtration. The precursor was washed until neutral and dried at 60°C. It was then transferred to a calcining furnace and calcined at 400°C for 4 hours to obtain the catalyst material.

[0057] Catalytic performance testing; catalytic performance testing in sintering flue gas The catalyst materials prepared in Examples 1-5 and Comparative Examples 1-8 were dispersed in water to form a paste. The paste was then coated onto a cordierite substrate using a vacuum coating method. The substrate dimensions were 2.5*2.5*1.7cm. After coating, the substrate was dried and calcined. The final catalyst loading was approximately 0.20g. The coated catalyst pieces were placed in a catalytic reactor and sintered flue gas containing water, SO2, and VOCs under the same operating conditions was introduced. The volume fractions of the flue gas components were: 0.76% CO, 16.8% O2, 10.5% H2O, 3.9ppm SO2, 142ppm CH4, 13ppm benzene-based VOCs, with the remainder being N2, and a space velocity of 10000h⁻¹. -1 The average temperature is 283℃.

[0058] The parameters and test results are shown in the table below:

[0059] Through experiments, the catalytic materials prepared in Examples 1-6 of this invention were subjected to continuous catalytic oxidation of CO in sintering flue gas containing water, SO2, and benzene-based VOCs. After 90 days, the sulfur resistance of all catalytic materials remained above 95%, and the carbon deposition resistance remained above 97%.

Claims

1. A silicate composite copper-manganese spinel catalytic material, characterized in that: This catalytic material is obtained by composite silicate on copper-manganese spinel through anisovalent substitution. Specifically, a copper source, a manganese source, and a silicon source are dissolved in a solvent to obtain a mixed solution, wherein the silicon source is silicon dioxide. An alkaline precipitant is added to the mixed solution to carry out the reaction. After the reaction is completed, solid-liquid separation is performed, and the obtained solid product is calcined to obtain a crude product. The crude product is first placed in an alkaline solution for reaction, and after the reaction is completed, it is calcined to obtain a silicate composite copper-manganese spinel catalytic material, wherein the alkaline precipitant is ammonia water; and the silicate is one or more of lithium silicate, sodium silicate, and potassium silicate.

2. The catalytic material according to claim 1, characterized in that: The chemical formula of the copper-manganese spinel is Cu. x Mn y O z Where x takes values ​​from 1 to 3, y takes values ​​from 1 to 4, and z takes values ​​from 3 to 12.

3. The catalytic material according to claim 1, characterized in that: The silicate is sodium silicate.

4. The catalytic material according to claim 3, characterized in that: In the catalytic material, the composite molar ratio of copper manganese spinel to sodium silicate is 1:0.05~0.

5.

5. A method for preparing the silicate composite copper-manganese spinel catalytic material as described in claim 1, characterized in that: The method includes the following steps: 1) A mixed solution is obtained by dissolving a copper source, a manganese source, and a silicon source in a solvent; the silicon source is silicon dioxide. 2) Add an alkaline precipitant to the mixed solution to carry out the reaction. After the reaction is completed, perform solid-liquid separation and calcine the obtained solid product to obtain a crude product; the alkaline precipitant is ammonia water; 3) First, the crude product is placed in an alkaline solution for reaction. After the reaction is completed, it is calcined to obtain a silicate composite copper-manganese spinel catalyst material.

6. The method according to claim 5, characterized in that: In step 1), the copper source is a soluble copper salt; and / or In step 1), the manganese source is a soluble manganese salt.

7. The method according to claim 6, characterized in that: In step 1), the copper source is one or more of copper sulfate, copper nitrate, copper chloride, and copper acetate; and / or In step 1), the manganese source is one or more of manganese sulfate, manganese nitrate, manganese chloride, and manganese acetate.

8. The method according to claim 7, characterized in that: In step 1), the copper source is copper acetate; and / or In step 1), the manganese source is manganese acetate; and / or In step 1), the silicon source is silicon dioxide nanoparticles.

9. The method according to claim 5, characterized in that: In step 1), the solvent is a mixed solvent consisting of water and ethanol; and / or In step 1), the molar ratio of copper source, manganese source and silicon source in the mixed solution is 0.8~2:0.8~2:1~6.

10. The method according to claim 9, characterized in that: In the mixed solvent, the molar ratio of water to ethanol is 1-2.5:0.1-1; and / or In step 1), the molar ratio of copper source, manganese source and silicon source in the mixed solution is 1~1.5:1~1.5:2~5.

11. The method according to claim 5, characterized in that: In step 2), the amount of ammonia added is 2 to 7 times the total molar amount of the copper and manganese sources; and / or In step 2), the calcination temperature is 350~550℃; the calcination time is 1~12h.

12. The method according to claim 11, characterized in that: In step 2), the amount of ammonia added is 3 to 6 times the total molar amount of the copper and manganese sources; and / or In step 2), the calcination temperature is 400~500℃; the calcination time is 2~10h.

13. The method according to claim 5, characterized in that: In step 3), the alkaline solution is an aqueous solution of lithium hydroxide, sodium hydroxide, and potassium hydroxide; the amount of alkaline solution added is such that the molar ratio of silicon to alkali in the crude product is 1~3.5:3~10; and / or In step 3), the calcination temperature is 350~550℃; the calcination time is 1~12h.

14. The method according to claim 13, characterized in that: In step 3), the alkaline solution is a sodium hydroxide solution with a concentration of not less than 1 mol / L; the amount of alkaline solution added is such that the molar ratio of silicon to alkali in the crude product is 1.3~3:4~9; and / or In step 3), the calcination temperature is 400~500℃; the calcination time is 2~10h.

15. The method according to claim 5, characterized in that: In step 3), the reaction temperature of the crude product in the alkaline solution is 40~80℃; the reaction time is 0.3-2h.

16. The method according to claim 15, characterized in that: In step 3), the reaction temperature of the crude product in the alkaline solution is 50~70℃; the reaction time is 0.5-1.5h.

17. The method according to any one of claims 5-16, characterized in that: Steps 1) to 3) are as follows: First, weigh out the copper source, manganese source, and silicon source according to the proportions, add them to a sufficient amount of solvent, stir to dissolve and mix evenly to obtain a mixed solution; then, under stirring, add an alkaline precipitant dropwise to the mixed solution to carry out the reaction. After the reaction is completed, filter to obtain a solid product. Wash the solid product until neutral and dry it at 40~200℃, then calcine it to obtain a crude product; finally, place the crude product in an alkaline solution under heating to carry out the reaction. After the reaction is completed, filter to obtain a precursor. Wash the precursor until neutral and dry it at 40~200℃, then calcine it to obtain a silicate composite copper-manganese spinel catalyst material.

18. The use of a silicate composite copper-manganese spinel catalyst material as described in any one of claims 1-4 or a silicate composite copper-manganese spinel catalyst material prepared by the method described in any one of claims 5-17, characterized in that: The silicate composite copper-manganese spinel catalyst material is used for the catalytic oxidation of CO.

19. The use according to claim 18, characterized in that: The silicate composite copper-manganese spinel catalyst material is used for the catalytic oxidation of CO in sintering flue gas.

Citation Information

Patent Citations

  • Supported copper-manganese-water-gas shift catalyst and preparation method thereof

    CN102688765B

  • Lanthanum-doped copper-manganese composite oxide catalyst and its preparation method

    CN109603842B

  • Oxide-modified copper-manganese spinel catalyst for CO oxidation and its preparation method

    CN112547085B

  • Ammonia-etched urchin-like spherical copper-manganese spinel material, its preparation method and application

    CN113046778B

  • A metal catalyst, its preparation method and application

    CN113145125B